Effect of Time Interval Between LEEP and Subsequent Hysterectomy on Postoperative Infectious Morbidity - Ni T; Meng Y; Li Y; Chen Q; Huang Y; Wang L; Qian X; Wang Y (Dove Medical Press, 2020)
Ting Ni,1 Yaping Meng,1 Yuhong Li,1 Qinfang Chen,1 Yong Huang,1 Lihua Wang,1 Xiaolei Qian,1 Yudong Wang1– 3 1Department of Gynecologic Oncology, International Peace Maternity and Child Health Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200030, People’s Republic of China; 2Shanghai Municipal Key Clinical Specialty, International Peace Maternity and Child Health Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200030, People’s Republic of China; 3Shanghai Key Laboratory of Embryo Original Disease, International Peace Maternity and Child Health Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200030, People’s Republic of ChinaCorrespondence: Yudong Wang Email owangyudong@126.comObjective: This study aimed to provide insight into the effect of time interval between loop electrosurgical excision procedure (LEEP) and subsequent hysterectomy on postoperative infectious morbidity in cervical neoplasia patients.Methods: In this retrospective cohort study, a total of 1172 medical records of patients who were diagnosed with high grade cervical intraepithelial neoplasia (HSIL) or invasive cancer underwent a subsequent hysterectomy after LEEP at the International Peace Maternity and Child Health Hospital (IPMCH) in Shanghai, China from January 2008 to December 2019 were collected. The study outcome was postoperative infectious morbidity within 30 days after a hysterectomy. Overall and surgical approach specific effect of time interval on infectious morbidity was estimated using logistic regression in crude and adjusted models.Results: There was an inverse association between time interval and postoperative infectious morbidity in HSIL or invasive cancer patients (OR=0.99, 95% CI: 0.98– 1.00, p=0.0079). When trisecting time interval into three parts, the top tertile time interval (34– 90 days) was also inversely associated with infectious morbidity compared with bottom tertile (0– 16 days), independent of stage, surgical approach, operative time and estimated blood loss (OR=0.66,95% CI: 0.43– 1.00, P=0.0487). A test for interaction between time interval and surgical approach on infectious morbidity was significant (P values for interaction= 0.0352). Longer time interval significantly reduced the risk of infectious morbidity in the laparoscopic group (OR = 0.37, 95% CI: 0.17– 0.78), while no statistically significant effects were observed in patients who underwent vaginal or open abdominal hysterectomy.Conclusion: The time interval and surgical approach can interactively affect the risk of postoperative infectious morbidity in cervical neoplasia patients who underwent a hysterectomy after LEEP. Our data suggest that compared with vaginal or open abdominal hysterectomy, laparoscopic hysterectomy required a longer time interval (34– 90 days) to reduce the risk of infectious morbidity.Keywords: time interval, LEEP, hysterectomy, cervical cancer